Abnormal interhemispheric resting state functional connectivity in Parkinson’s disease patients with impulse control disorders - Caiting Gan (Nature Portfolio, 2021)
Abstract Impulse control disorders (ICD) in Parkinson’s disease (PD) might be attributed to misestimate of rewards or the failure to curb inappropriate choices. The mechanisms underlying ICD were reported to involve the lateralization of monoamine network. Our objective was to probe the significant role of lateralization in the pathogenesis of ICD. Twenty-one PD patients with ICD (PD-ICD), thirty-three without ICD (PD-no ICD), and thirty-seven healthy controls (HCs) were recruited and performed T1-weighted, diffusion tensor imaging (DTI) scans and resting state functional magnetic resonance imaging (rs-fMRI). By applying the Voxel-mirrored Homotopic Connectivity (VMHC) and Freesurfer, we evaluated participants’ synchronicity of functional connectivity and structural changes between hemispheres. Also, tract-based spatial statistics (TBSS) was applied to compare fiber tracts differences. Relative to PD-no ICD group, PD-ICD group demonstrated reduced VMHC values in middle frontal gyrus (MFG). Compared to HCs, PD-ICD group mainly showed decreased VMHC values in MFG, middle and superior orbital frontal gyrus (OFG), inferior frontal gyrus (IFG) and caudate, which were related to reward processing and inhibitory control. The severity of impulsivity was negatively correlated with the mean VMHC values of MFG in PD-ICD group. Receiver operating characteristic (ROC) curves analyses uncovered that the mean VMHC values of MFG might be a potential marker identifying PD-ICD patients. However, we found no corresponding asymmetrical alteration in cortical thickness and no significant differences in fractional anisotropy (FA) and mean diffusivity (MD). Our results provided further evidence for asymmetry of functional connectivity in mesolimbic reward and response inhibition network in ICD.